2020
DOI: 10.1590/1516-4446-2019-0471
|View full text |Cite
|
Sign up to set email alerts
|

Trichotillomania is more related to Tourette disorder than to obsessive-compulsive disorder

Abstract: Objective: Trichotillomania (TTM) is characterized by the pulling out of one's hair. TTM was classified as an impulse control disorder in DSM-IV, but is now classified in the obsessive-compulsive related disorders section of DSM-5. Classification for TTM remains an open question, especially considering its impact on treatment of the disorder. In this review, we questioned the relation of TTM to tic disorder and obsessive-compulsive disorder (OCD). Method: We reviewed relevant MEDLINE-indexed articles on clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 269 publications
(387 reference statements)
0
10
0
4
Order By: Relevance
“…Hence, scratching in Sapap3 -/mice demonstrates tic-like elements but cannot be entirely defined as such. This tic-close but not entirely tic-like status makes scratching similar to pathological hair-pulling and skin-picking, which has propagated a wave of clinical discussion concerning these phenotypes in human trichotillomania patients as well as frequently comorbid OCD and/or Tourette Syndrome patients with hair-pulling and/or skin-picking pathologies (5). Interestingly, although no direct link was found between genetic SAPAP3 variants and OCD, identified single nucleotide polymorphisms were associated with grooming disorders such as pathologic nail biting, pathologic skin picking, and/or trichotillomania, an obsessive-compulsive related disorder (50,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, scratching in Sapap3 -/mice demonstrates tic-like elements but cannot be entirely defined as such. This tic-close but not entirely tic-like status makes scratching similar to pathological hair-pulling and skin-picking, which has propagated a wave of clinical discussion concerning these phenotypes in human trichotillomania patients as well as frequently comorbid OCD and/or Tourette Syndrome patients with hair-pulling and/or skin-picking pathologies (5). Interestingly, although no direct link was found between genetic SAPAP3 variants and OCD, identified single nucleotide polymorphisms were associated with grooming disorders such as pathologic nail biting, pathologic skin picking, and/or trichotillomania, an obsessive-compulsive related disorder (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The exact nature of pathological RB is not always trivial to distinguish and comorbidities impede correct diagnosis and appropriate treatment. This applies especially to three neuropsychiatric disorders with high comorbidity (1)(2)(3): Tourette Syndrome (TS), a childhood-onset neurodevelopmental disorder characterized by tics, Obsessive Compulsive Disorder (OCD), a heterogeneous disorder, of which the most typical form is characterized by obsessions and obsession-dependent compulsions (4), as well as trichotillomania (TTM), which has proven difficulty in its classification as belonging to a ticor compulsive-like nature (5). Tics, defined as sudden, rapid, recurrent, non-rhythmic motor events (4), and compulsions, defined as non-rhythmic, but less sudden RBs are easily confounded in clinical practice (3,6).…”
Section: Introductionmentioning
confidence: 99%
“…Rodent self-grooming is now widely recognised as a suitable behavioural output for studying the neural circuits underlying the generation of complex patterns of repetitive behaviours that may be relevant to human psychiatric disorders (4) and, over the last ten years, it has been suggested that some transgenic mice characterised by aberrant repetitive grooming behaviour can be used as models of OCD or OCD spectrum disorders. The grooming behaviour of VMAT2-deficient mice has some similarities to that identified in mice lacking synapse-associated protein 90/postsynaptic density protein 5-associated protein 3 (SAPAP3-/-) (67), which essentially consists of a pathologically increased number of short grooming sessions. The complex sequenced structure of mouse self-grooming is characterised by repeated stereotyped movements or "syntactic chains" (68) that start of a series of elliptical bilateral paw strokes near the nose (paw and nose grooming) and a series of unilateral paw strokes from the mystacial vibrissae to below the eye (face grooming), followed by a series of simultaneous bilateral strokes backwards and upwards (head grooming) and body licking.…”
Section: Discussionmentioning
confidence: 88%
“…se asoció a los tics y al síndrome de Gilles de la Tourette, pero en el DSM-V se incluyó dentro del espectro de los trastornos obsesivo-compulsivos (TOC) y de los trastornos relacionados TOC: acumulación, excoriación y dismórfico corporal. Actualmente, no existe un acuerdo unánime en relacionarlo con los tics o con los TOC [6][7][8] . Son cinco los criterios que se deben cumplir para un diagnóstico de tricotilomanía: a) arrancarse el cabello de modo recurrente; b) intentos repetidos e infructuosos de detener el tirón de pelo; c) causa malestar; d) interferir en alguna área de la vida del que lo padece; e) no es atribuible a otra causa médica o trastorno mental 4,6 .…”
Section: En El Diagnostic and Statistical Manual Of Mental Disorder I...unclassified